Advances in Carpal Tunnel Syndrome: Anatomy, Ultrasound Diagnostics and Modern Treatment Strategies - review - Sitarek, Gracjan; Żerek, Marta (Journal of Education, Health and Sport, 2025)
Carpal Tunnel Syndrome (CTS) is a prevalent condition characterized by compression of the median nerve within the carpal tunnel, leading to motor and sensory dysfunctions primarily in the hand. The advent of high-resolution ultrasound (US) has revolutionized the diagnostic approach to CTS, offering a non-invasive alternative to traditional nerve conduction studies (NCS). This review examines the anatomical foundations of CTS, explores the diagnostic value of ultrasound compared to NCS, and evaluates its role in guiding therapeutic interventions, both conservative and surgical. Recent studies highlight the growing importance of ultrasound in diagnosing CTS and tailoring individualized treatment strategies, with a focus on improving patient outcomes and reducing recovery times. The review also emphasizes advancements in ultrasound-guided surgical techniques, demonstrating improved efficacy and fewer complications in severe cases of CTS.